Peningkatan Sarana Pendidikan Melalui Kegiatan Pengecetan Ulang TPQ Al Munawarah : Pengabdian - M. Umar Faqieh; Ilma Nur Rizqi; Muammar; Muhamad Yunus; Wahidin (Jurnal Pengabdian Masyarakat dan Riset Pendidikan, 2025)
This community service activity aimed to improve the quality of educational facilities through the repainting of the Al-Munawarah Qur’anic Education Center (TPQ) building, located in Kuta Village, Belik District, Pemalang Regency. As a non-formal educational institution, TPQ plays a strategic role in shaping children’s character and morality. However, the deteriorating condition of the building had reduced the comfort and learning motivation of the students. The program was carried out from August 20 to 24, 2025, by a team from Universitas Muhadi Setiabudi Brebes, with the scope of work covering volume calculation, land clearing, and room painting. The results showed an improvement in the quality of the learning environment, which became cleaner, more attractive, and more comfortable, while also fostering community awareness of the importance of educational facilities. The repainting effort proved effective in creating a more conducive learning atmosphere.